Impact of COVID-19 on Stock Market in Tourism Sector and the Effect on Earnings Management - Ladislav VAGNER (Communications of International Proceedings, 2021)
Travel restrictions related to the COVID-19 pandemic have significantly decimated the tourism sector. Given the situation regarding COVID-19 and its impact on the global economy, we decided to analyze stock value development's effects on the stock market. The pandemic began to spread from China and gradually erupted into a global problem. Restrictions have caused social distancing, closed borders, schools, shops, restaurants, travel agencies on the rise in hospitals. Regarding all areas, the tourism sector has been most crippled, so we have focused on this sector. Specifically, our attention was focused on developing the shares of two companies in the aviation industry and companies in the cruise ship industry. The development of selected shares changed rapidly between January and March and influenced income, leading to earnings management changes. The focus was mainly on results from October 2019 to December 2020 of these companies.
Keywords: Stock Market; COVID-19; Tourism Sector; Earnings Management.